A Brief Review of the Nutritive Value and Chemical Components of Bat Guano and Its Potential Use as a Natural Fertiliser in Agriculture - Siti Syamim Nurfatihah, Abd Rahman; Roberta Chaya Tawie, Tingga; Mohamad Fhaizal, Mohamad Bukhori; Sharifah Mona, Abd Aziz Abdullah (Universiti Malaysia Sarawak, 2023)
New and improved fertilisers are constantly being introduced to the market to help increase crop yields. However, the common usage of chemical fertilisers had brought upon negative impacts to the environment and the study for sustainable fertiliser is still ongoing. This review will highlight the usage of bat guano as a valuable fertiliser which has a potential to diminish the effects of chemical fertiliser usage, increase yield and is cost effective. Its role as a fertiliser can support the agricultural growth and in turn provides additional care for plants. The chemical compositions of guano which was found to be subpar with other fertilisers support its usage of guano as an alternative for crop yield enhancement. Plant growth performance that shows a significant positive impact of guano on crops, further demonstrates its usage as organic fertilisers. In-depth study of the chemical composition of guano should be pursued as the fertiliser has high beneficial value to the ecology and economy.